2012
DOI: 10.1287/mnsc.1120.1538
|View full text |Cite
|
Sign up to set email alerts
|

Coordination of Price Promotions in Complementary Categories

Abstract: In this paper, I investigate the outcome of a price competition between two firms, each producing two complementary products. Specifically, I study each firm's decision to coordinate price promotions of its products. Consumers are divided into loyals, who purchase both products from their preferred firm, and heterogeneous switchers, who choose between four possible bundles or buy a product in a single category. The switchers are willing to pay some price premium in order to purchase two complementary products … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 27 publications
2
12
0
Order By: Relevance
“…of their products. This implication is consistent with the findings in Sinitsyn (2012), who reports that in cake mix and cake frosting categories where the firms use umbrella branding, the promotions of complementary products are highly correlated. On the other hand, in detergent and fabric softener categories, where the firms use individual branding (P&G produces detergent Tide, fabric softeners Bounce and Downy; Unilever produces detergents Surf and Wisk, fabric softener Snuggle), price promotions were not coordinated.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…of their products. This implication is consistent with the findings in Sinitsyn (2012), who reports that in cake mix and cake frosting categories where the firms use umbrella branding, the promotions of complementary products are highly correlated. On the other hand, in detergent and fabric softener categories, where the firms use individual branding (P&G produces detergent Tide, fabric softeners Bounce and Downy; Unilever produces detergents Surf and Wisk, fabric softener Snuggle), price promotions were not coordinated.…”
Section: Discussionsupporting
confidence: 92%
“…If the firms use umbrella branding, which is one of the strategies that is likely to significantly increase the degree of complementarity, then the firms should try to use other strategies, such as joint promotions, in an attempt to further increase the perceived complementarity of their products. This implication is consistent with the findings in Sinitsyn (), who reports that in cake mix and cake frosting categories where the firms use umbrella branding, the promotions of complementary products are highly correlated. On the other hand, in detergent and fabric softener categories, where the firms use individual branding (P&G produces detergent Tide, fabric softeners Bounce and Downy; Unilever produces detergents Surf and Wisk, fabric softener Snuggle), price promotions were not coordinated.…”
Section: Discussionsupporting
confidence: 91%
“…Compared to previous studies that have undertaken this task (Fosfuri & Giarratana, 2009;Eaton et al, 2011), we add insights from a more competitive environment in which companies' product portfolio composition and brand postures are very heterogeneous, thus offering a more complex comprehensive picture of the possible effects of product and brand strategies on firms' market performance. In doing so, we also integrate marketing perspectives in strategy literature analyzing firm performance, thus answering to the recent call for a more explicit account of the role of marketing actions in the study of firms' strategic interactions in a competitive landscape (De Figueiredo & Kyle, 2006;Hui, 2004;Sinitsyn, 2012;Barroso & Giarratana, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Second, building on recent strategy literature (De Figueiredo & Kyle, 2006;Hui, 2004;Sinitsyn, 2012;Barroso & Giarratana, 2013), our paper integrates the role of marketing actions in the literature on firm's performance. While in the past, strategy scholars have focused mainly on other types of competitive moves, such as product launches, product retirements and R&D investments, recent research has demonstrated the importance of accounting for firms' marketing strategies as they can complement our understanding of the drivers of firm performance in a competitive landscape.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, depending on the price of the product, consumers' source of blame shifts from self to the retailer or manufacturer. Furthermore, research on complementary categories (Sinitsyn 2012) demonstrates that switchers are willing to pay a price premium for complementary products as they infer better match between the products due to the same brand name. Hence, we investigate the role of price in the exchange and refund decisions.…”
Section: Exchange or Refundmentioning
confidence: 99%